Construction of a Conductive Polymer/AuNP/Cyanobacteria-Based Biophotovoltaic Cell Harnessing Solar Energy to Generate Electricity via Photosynthesis and Its Usage as a Photoelectrochemical Pesticide Biosensor: Atrazine as a Case Study - Buyukharman, Mustafa; Mulazimoglu, Ibrahim Ender; Yıldız, Hüseyin Bekir (Amer Chemical Soc, 2024)
In this research, a cyanobacteria (Leptolyngbia sp.)-based biological photovoltaic cell (BPV) was designed. This clean energy-friendly BPV produced a photocurrent as a result of illuminating the photoanode and cathode electrodes immersed in the aqueous medium with solar energy. For this purpose, both electrodes were first coated with conductive polymers with aniline functional groups on the gold electrodes. In the cell, the photoanode was first coated with a gold-modified poly 4-(2,5-di(thiophen-2-yl)-1H-pyrrol-1-yl)benzamine polymer, P(SNS-Aniline). Thioaniline-functionalized gold nanoparticles were used to provide a cross-link formation with bis-aniline conductive bonds with the conductive polymer using electrochemical techniques. Leptolyngbia sp., one of the cyanobacteria that can convert light energy into chemical energy, was attached to this layered electrode surface. The cathode of the cell was attached to the gold electrode surface with P(SNS-Aniline). Then, the bilirubin oxidase (BOx) enzyme was immobilized on this film surface with glutaraldehyde activation. This cell, which can use light, thanks to cyanobacteria, oxidized and split water, and oxygen was obtained at the photoanode electrode. At the cathode electrode, the oxygen gas was reduced to water by the bioelectrocatalytic method. To obtain a high photocurrent from the BPV, necessary optimizations were made during the design of the system to increase electron transport and strengthen its transfer. While the photocurrent value obtained with the designed BPV in optimum conditions and in the pseudosteady state was 10 mA/m2, the maximum power value obtained was 46.5 mW/m2. In addition to storing the light energy of the system, studies have been carried out on this system as a pesticide biosensor. Atrazine biosensing via the BPV system was analytically characterized between 0.1 and 1.2 mu M concentrations for atrazine, and a very low detection limit was found as 0.024 mu M. In addition, response time and recovery studies related to pesticide biosensor properties of the BPV were also investigated.
Keywords: High-Efficiency; Photocurrent; Polymer; Communication; Degradation; Water; Sp.